The Concept of Feminism in Islamic Education - Nida Farhani Mubarokah; Nisaul Hasanah; Uswatun Mahmudah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
The Spread of the Western feminism movement in parts of the world including Indonesia has had a fairly risky impact on Indonesian society, especially among women. The influence of western feminism is the equalization of positions between men and women in all respects so that not women in Indonesia forget their nature as women both when they become daughters, wives, and mothers so that this often leads to conflict in the family that are contrary to Islamic teachings. This article aims to find the real concept of feminism in Islam. To obtain answers to these problems, the researchers used literature studies namely reviewing various scientific articles related to Western and Islamic feminism as well as reciting verses from the Quran related to equality of men and women. The result obtained from the study stated that the concept of feminism in Islam aims to make women knowledgeable and insightful and not narrow their space of movement. But not just standing alone without needing a partner or a man. Both are creatures of Allah who need each other and were created to perfect each other. In Islam, the nature of men and women is different and there is a nature that can only be done by men or women. Therefore, feminism in Islam only demands equality of rights such as the right to study, the right to work, and the right to a career, not demanding gender equality.